Back contact solar cell, preparation method thereof and cell module

By adopting a stacked anti-reverse layer structure on the front of the back contact solar cell, and using the combination of a silicon nitride layer and a carbon-doped silicon nitride layer, the problem of unstable thickness of the anti-reverse layer is solved, and the corrosion resistance and optical performance of the battery are improved.

CN119894109AActive Publication Date: 2025-04-25GOLDEN SOLAR (QUANZHOU) NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202510353015.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-25
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The thickness of the front anti-reflection layer of the existing back contact solar cells is unstable, resulting in a decrease in the short-circuit current density and affecting the battery performance.

Method used

A stacked anti-reflection layer structure is adopted, including a silicon nitride layer and a carbon-doped silicon nitride layer. The acid resistance of the film layer is improved by doping carbon, and the refractive index is reduced in sequence by adjusting the refractive index, thereby maintaining the optical effect of the anti-reflection layer on the front of the battery.

Benefits of technology

It improves the corrosion resistance of the film layer, maintains the stability and consistency of the process, and enhances the optical and electrical properties of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894109A_ABST
    Figure CN119894109A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solar cells, and particularly relates to a back contact solar cell, a preparation method thereof and a cell assembly, in the back contact solar cell, a carbon-doped silicon nitride layer is arranged on a silicon nitride layer on a passivation layer, and the carbon-doped silicon nitride layer has relatively strong acid resistance, so that the carbon-doped silicon nitride layer has relatively strong acid resistance in a texturing cleaning solution; the film can not be corroded by strong base and is not easily corroded by strong acid, and the corrosion rate of the film in HF acid is reduced, so that the corrosion resistance of the subsequent film in a solution is facilitated, the stability and the consistency of a manufacturing process are kept, and the production yield is improved; and meanwhile, the refractive indexes of the silicon nitride layer and the carbon-doped silicon nitride layer included in the laminated anti-reflection layer are sequentially reduced from inside to outside, so that the optical effect of the anti-reflection layer on the front surface of the battery is favorably maintained, and the optical performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a back-contact solar cell and a preparation method thereof, and a cell assembly. Background Art

[0002] During the preparation of existing back-contact solar cells, after the third semiconductor layer and the anti-reflection layer are formed on the front side of the silicon wafer, wet chemical cleaning is performed. To ensure a good anti-reflection effect, the top layer of the existing anti-reflection layer generally adopts a nitrogen-rich silicon nitride film layer (nitrogen-rich means that the nitrogen content is relatively high, and the refractive index of nitrogen-rich silicon nitride is generally below 1.98). However, the nitrogen-rich silicon nitride film layer generally has poor resistance to solution corrosion. When the concentration of the solution fluctuates due to factors such as liquid replenishment or temperature, the film thickness of the anti-reflection layer will fluctuate greatly, and the anti-reflection effect will be greatly reduced, thereby causing the short-circuit current density of the battery to decrease, affecting the battery performance.

[0003] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention

[0004] The purpose of the present invention is to provide a back-contact solar cell and a preparation method and a cell assembly, so as to solve the technical problem that the thickness of the anti-reflection layer on the front side of the solar cell is unstable, resulting in a decrease in the short-circuit current density.

[0005] In order to achieve the above objectives, in a first aspect, the present invention provides a back-contact solar cell, comprising: A silicon wafer having a front side and a back side; A first semiconductor layer is arranged on the back side of the silicon wafer, the first semiconductor layer comprises a tunneling silicon oxide layer and an N-type doped polysilicon layer sequentially formed on the back side of the silicon wafer; the first semiconductor layer is separated by a plurality of second semiconductor opening regions, the second semiconductor opening regions and the surface of the first semiconductor layer around the second semiconductor opening regions are covered with the second semiconductor layer; a first semiconductor opening region is provided between adjacent second semiconductor opening regions, the first semiconductor opening region separates the second semiconductor layer; A passivation layer and a stacked anti-reflection layer, wherein the passivation layer and the stacked anti-reflection layer are sequentially arranged on the front side of the silicon wafer; wherein the stacked anti-reflection layer comprises a silicon nitride layer and a carbon-doped silicon nitride layer, and the silicon nitride layer is closer to the passivation layer than the carbon-doped silicon nitride layer; the total thickness of the stacked anti-reflection layer is 80-130 nm, wherein the thickness of the silicon nitride layer is 50-120 nm, and the refractive index is 1.9-2.2; the thickness of the carbon-doped silicon nitride layer is 1-50 nm, and the refractive index is 1.7-1.9.

[0006] Optionally, the carbon-doped silicon nitride layer is a carbon-doped silicon nitride film layer with the same concentration, and the carbon doping concentration is 1×10 18 ~9×10 19 cm -3 .

[0007] Optionally, the carbon-doped silicon nitride layer has a carbon-doped concentration that gradually increases from a side close to the silicon wafer to a side away from the silicon wafer, and the carbon-doped concentration ranges from low to high, and is 1×10 18 ~9×10 19 cm -3 .

[0008] Optionally, the first semiconductor layer includes a tunneling silicon oxide layer and an N-type doped polysilicon layer, the tunneling silicon oxide layer has a thickness of 1-2 nm, and the N-type doped polysilicon layer has a thickness of 80-140 nm.

[0009] Optionally, a width of the first semiconductor opening region is 400 μm to 600 μm, and a width of the second semiconductor opening region is 200 μm to 300 μm.

[0010] Optionally, the back-contact solar cell also includes: an insulating groove; the insulating groove is located between the adjacent first semiconductor opening area and the second semiconductor opening area; the first semiconductor opening area and the second semiconductor layer are both covered with a transparent conductive film layer, and the insulating groove separates the transparent conductive film layer located in the first semiconductor opening area from the transparent conductive film layer located on the second semiconductor layer.

[0011] In a second aspect, the present invention further provides a method for preparing a back-contact solar cell, which is used to prepare the back-contact solar cell as described in the first aspect, comprising: S1. Provide a double-sided polished silicon wafer; S2, forming a first semiconductor layer and a mask layer on the back side of the silicon wafer; S3, etching an opening on the back side of the silicon wafer for the first time to form a second semiconductor opening region; S4, texturing and cleaning the front and back opening areas of the silicon wafer; S5, forming a passivation layer and a laminated anti-reflection layer on the front side of the silicon wafer; the laminated anti-reflection layer comprises a silicon nitride layer and a carbon-doped silicon nitride layer sequentially formed on the passivation layer; The deposition temperature of the stacked anti-reflection layer is 350-600° C., wherein when depositing the silicon nitride layer, the mass flow rate of silane is 800-2000 sccm, the mass flow rate of ammonia is 6000-15000 sccm, the deposition pressure is 1300-2500 mtorr, and the power is 5 kW-20 kW; when depositing the carbon-doped silicon nitride layer, the mass flow rate of silane is 800-2000 sccm, the mass flow rate of ammonia is 6000-15000 sccm, the mass flow rate of methane is 500-2000 sccm, the deposition pressure is 1300-2500 mtorr, and the power is 5 kW-20 kW; S6, removing the back side coating and cleaning the second semiconductor opening area; The method of removing the back side coating and cleaning the second semiconductor opening area adopts HF acid solution, wherein the mass percentage of HF acid in the HF acid solution is 1% to 10%, the mass percentage of deionized water is 90% to 99%, the processing temperature is 20° C. to 30° C., and the removal time is 30 to 500 seconds; S7, forming a second semiconductor layer on the back side of the silicon wafer; S8, etching an opening on the back side of the silicon wafer for the second time to form a first semiconductor opening region; S9, depositing a transparent conductive film layer on the back side of the silicon wafer; S10, etching an opening on the back side of the silicon wafer for the third time to form an insulating groove; S11, forming metal electrodes at the first semiconductor opening and the second semiconductor opening on the back side of the silicon wafer respectively.

[0012] Optionally, the refractive index N of the silicon nitride layer and the carbon-doped silicon nitride layer in the stacked anti-reflection layer has a certain positive correlation with the corrosion rate C1 (Å / S) thereof in HF, specifically: The etching rate relationship between the refractive index of the silicon nitride layer and the carbon-doped silicon nitride layer in 5% HF is: N = 1.91 + 0.0319*C1 + 1.461*(C1~0.79125) 2 + 5.427*(C1~0.791) 3 .

[0013] Optionally, the cleaning time t≤D / (9C2), t is in S, D is the total thickness of the laminated anti-reflection layer in Å, and C2 is the average corrosion rate of the laminated anti-reflection layer in 5% HF acid.

[0014] Optionally, in step S4, it includes: The texturing liquid is a mixture of potassium hydroxide or sodium hydroxide, a texturing additive and water, wherein the mass percentage of potassium hydroxide or sodium hydroxide is 1% to 5%, and the mass percentage of the texturing additive is 0.5% to 1%. The texturing time is 10 to 60 minutes, and the texturing temperature is 70°C to 85°C.

[0015] Optionally, in step S4, it further includes: During the texturing and cleaning process, the first mask layer on the back of the silicon wafer is also removed through the final cleaning solution. The solution used to remove the first mask layer is HF acid solution. The mass percentage of HF acid in the HF acid solution is 0.5%~5%, the mass percentage of hydrogen peroxide is 3%~10%, and the mass percentage of deionized water is 95%~99.5%. The processing temperature is 20℃~30℃, and the removal time is 60s~500s.

[0016] In a third aspect, the present invention further provides a battery assembly, comprising: a back-contact solar cell as described in the first aspect.

[0017] The embodiments of the present invention have at least the following beneficial effects: The present invention adopts the above-mentioned technical scheme, by carbon-doping the silicon nitride layer, so that the carbon-doped silicon nitride film layer has strong acid resistance. In the texturing cleaning solution, it can neither be corroded by strong alkali nor easily corroded by strong acid, thereby reducing the corrosion rate of the film layer in HF acid. This is beneficial to the corrosion resistance of the subsequent film layer in the solution, maintaining the stability and consistency of the process, and improving the production yield. At the same time, by arranging the silicon nitride layer and the carbon-doped silicon nitride layer included in the stacked anti-reflection layer to decrease the refractive index from the inside to the outside in sequence, it is beneficial to maintain the optical effect of the anti-reflection layer on the front side of the battery and improve the optical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 A schematic diagram of the structure of a back-contact solar cell provided by an embodiment of the present invention; Figure 2 A schematic diagram of the relationship between the refractive index of a film layer of a back-contact solar cell and the corrosion rate of the film layer in HF acid provided by an embodiment of the present invention; Figure 3 A schematic flow chart of a method for preparing a back-contact solar cell provided in an embodiment of the present invention.

[0020] In the figure: 1-silicon wafer; 2-tunneling silicon oxide layer; 3-type doped polysilicon layer; 4-passivation layer; 5-stacked anti-reflection layer; 51-silicon nitride layer; 52-carbon-doped silicon nitride layer; 6-intrinsic hydrogenated amorphous silicon layer; 7-P-type doped amorphous silicon layer or P-type microcrystalline silicon layer; 8-transparent conductive film layer; 9-metal electrode. DETAILED DESCRIPTION

[0021] In the present invention, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0022] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0023] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all mean that they may be included or not included (or may be present or not).

[0024] like Figure 1 As shown, an embodiment of the present invention provides a back contact solar cell, comprising: A silicon wafer 1 having a front side and a back side. As a base layer, the silicon wafer 1 is generally polished to improve the bonding strength of subsequent film layers, thereby improving the stability of the film layers. The first semiconductor layer is arranged on the back of the silicon wafer 1, and the first semiconductor layer includes a tunneling silicon oxide layer 2 and an N-type doped polysilicon layer 3 sequentially formed on the back of the silicon wafer 1. The first semiconductor layer is separated by a plurality of second semiconductor opening regions W2, and the second semiconductor opening regions W2 and the surface of the first semiconductor layer around the second semiconductor opening regions are covered with the second semiconductor layer. A first semiconductor opening region W1 is provided between adjacent second semiconductor opening regions, and the first semiconductor opening region W1 separates the second semiconductor layer, and the semiconductor film layers of the first semiconductor region and the second semiconductor region eventually form the P region and N region of the solar cell. The passivation layer 4 and the laminated anti-reflection layer 5 are sequentially arranged on the front side of the silicon wafer 1. The laminated anti-reflection layer 5 comprises a silicon nitride layer 51 and a carbon-doped silicon nitride layer 52. The silicon nitride layer 51 is closer to the passivation layer 4 than the carbon-doped silicon nitride layer 52, that is, the silicon nitride layer 51 is closer to the inside and the carbon-doped silicon nitride layer 52 is closer to the outside, so as to protect the inner silicon nitride layer 51. The total thickness of the laminated anti-reflection layer 5 is 80-130 nm, the thickness of the silicon nitride layer 51 is 50-120 nm, and the refractive index is 1.9-2.2; the thickness of the carbon-doped silicon nitride layer 52 is 1-50 nm, and the refractive index is 1.7-1.9.

[0025] like Figure 2 is a schematic diagram showing the relationship between the refractive index of the carbon-doped silicon nitride layer 52 and its corrosion rate in HF acid. Figure 2 It can be seen that the refractive index of the film layer in the present invention is positively correlated with the corrosion rate of the film layer in HF, that is, the smaller the refractive index of the film layer, the slower the corresponding corrosion rate. Therefore, reducing the refractive index of the film layer by carbon doping is beneficial to reducing the corrosion rate, thereby protecting the inner silicon nitride layer 51 and further improving the film stability of the silicon nitride layer 51.

[0026] It should be noted that the carbon-doped silicon nitride layer 52 is formed by doping carbon when preparing silicon nitride. The specific implementation of carbon doping is, for example, adding methane to the reaction gas used to prepare the silicon nitride layer 51 .

[0027] In the back-contact solar cell of the present invention, by carbon-doping the silicon nitride layer 51, the carbon-doped silicon nitride film layer has strong acid resistance. In the texturing and cleaning solution, it can neither be corroded by strong alkali nor easily corroded by strong acid, thereby reducing the corrosion rate of the film layer in HF acid (hydrofluoric acid). This is beneficial to the corrosion resistance of the subsequent film layer in the solution, maintaining the stability and consistency of the process, and improving the production yield. At the same time, by arranging the silicon nitride layer 51 and the carbon-doped silicon nitride layer 52 included in the stacked anti-reflection layer 5, the refractive index decreases from the inside to the outside, which is beneficial to maintaining the optical effect of the anti-reflection layer on the front side of the battery and improving the optical performance.

[0028] Optionally, the carbon-doped silicon nitride layer 52 is a carbon-doped silicon nitride film layer with the same concentration throughout, that is, the doping concentration of each region of the carbon-doped silicon nitride layer 52 is the same, and the carbon doping concentration is 1×10 18 ~9×10 19 cm -3 .

[0029] Optionally, the carbon-doped silicon nitride layer 52 has a carbon-doping concentration that gradually increases from a side close to the silicon wafer 1 to a side away from the silicon wafer 1 , that is, the carbon-doping concentration is lower near the inner layer and higher near the outer layer.

[0030] Optionally, the carbon doping concentration ranges from low to high 1×10 18 ~9×10 19 cm -3 , that is, the carbon doping concentration varies within this range. Specifically, for every increase of 1 / 3-1 / 5 of the thickness, the doping concentration is 0.5-4 times the doping concentration of the previous layer. For example, the initial concentration is 1×10 18 cm -3 , the doping concentration of each 1 / 3 thickness is 2.5 times the doping concentration of the previous layer, so the concentration gradient is 1×10 18 cm -3 , 2.5×10 18 cm -3 , 6.25×10 18 cm -3 The increase in doping concentration gradient is beneficial to improving the corrosion resistance of the film while ensuring the optical effect.

[0031] Optionally, the thickness ratio of the silicon nitride layer 51 to the carbon-doped silicon nitride layer 52 is 1:(0.0083-1), and the etching rate of the carbon-doped silicon nitride layer 52 in a 5% HF solution is ≤0.05nm / s. By controlling the appropriate film thickness ratio and etching rate, it is beneficial to improve the stability and yield of the process while taking into account the optical effect.

[0032] Optionally, the first semiconductor layer includes a tunneling silicon oxide layer 2 and an N-type doped polysilicon layer 3, the tunneling silicon oxide layer 2 has a thickness of 1-2 nm, and the N-type doped polysilicon layer 3 has a thickness of 80-140 nm.

[0033] Optionally, a width of the first semiconductor opening region is 400 μm to 600 μm, and a width of the second semiconductor opening region is 200 μm to 300 μm.

[0034] Optionally, the back contact solar cell further comprises: an insulating groove; the insulating groove is located between the adjacent first semiconductor opening region and the second semiconductor opening region. The first semiconductor opening region and the second semiconductor layer are both covered with a transparent conductive film layer 8, and the insulating groove separates the transparent conductive film layer 8 located in the first semiconductor opening region from the transparent conductive film layer 8 located on the second semiconductor layer.

[0035] The second aspect, such as Figure 3 As shown, an embodiment of the present invention further provides a method for preparing a back-contact solar cell, which is used to prepare the back-contact solar cell as described in the above embodiment, and the preparation method comprises: S1. Provide a double-sided polished silicon wafer 1.

[0036] Specifically, the silicon wafer 1 has a front side and a back side, which are realized by polishing the front side and the back side of the silicon wafer 1; wherein the front side refers to the light-receiving surface of the silicon wafer 1, and the back side is the opposite back side of the light-receiving surface. In the embodiment of the present invention, the side close to the silicon wafer 1 is usually considered as the inside, and the side far from the silicon wafer 1 is considered as the outside. Optionally, the silicon wafer 1 is an N-type single crystal silicon wafer 1, for example: a Czochralski single crystal silicon wafer 1 or a cast single crystal silicon wafer 1.

[0037] S2, forming a first semiconductor layer and a mask layer on the back side of the silicon wafer 1.

[0038] Optionally, the first semiconductor layer comprises a tunneling silicon oxide layer 2 and an N-type doped polysilicon layer 3, the thickness of the tunneling silicon oxide layer 2 is 1-2 nm, and the thickness of the N-type doped polysilicon layer 3 is 80-140 nm. The tunneling silicon oxide layer 2 and the N-type doped polysilicon layer 3 are both formed by sequentially depositing and high-temperature annealing in a tubular polysilicon deposition furnace, and the deposition temperature is 400-500°C. When depositing the tunneling oxide layer, the mass flow rate of nitrous oxide is 8000-1200sccm, the pressure is 100-200pa, the power is 3-20KW, and the time is 20-100 seconds; when depositing the N-type doped polysilicon layer 3, the mass flow rate of silane is 1000-3000sccm, the mass flow rate of phosphine (2% PH3 and 98% H2) is 1000-2500sccm, the mass flow rate of hydrogen is 7000-9000sccm, the pressure is 100-300pa, the power is 5-20KW, and the time is 800-1300 seconds.

[0039] S3, etching an opening on the back side of the silicon wafer 1 for the first time to form a second semiconductor opening region.

[0040] Optionally, the first etching opening can be performed by laser or mask etching, as long as the second semiconductor opening area can be formed; wherein the laser can be an ultraviolet or green laser with a pulse width less than 10ns, and the width of the formed second semiconductor opening area is 400-600um.

[0041] S4, texturing and cleaning the front and back opening areas of the silicon wafer 1.

[0042] Specifically, the texturing liquid is a mixture of potassium hydroxide or sodium hydroxide, a texturing additive and water, wherein the mass percentage of potassium hydroxide or sodium hydroxide is 1% to 5%, and the mass percentage of the texturing additive is 0.5% to 1%. The texturing time is 10 to 60 minutes, and the texturing temperature is 70°C to 85°C.

[0043] S5, forming a passivation layer 4 and a laminated anti-reflection layer 5 on the front side of the silicon wafer 1; the laminated anti-reflection layer 5 comprises a silicon nitride layer 51 and a carbon-doped silicon nitride layer 52 which are sequentially formed on the passivation layer 4. The deposition temperature of the stacked anti-reflection layer 5 is 350-600° C., wherein when the silicon nitride layer 51 is deposited, the mass flow rate of silane is 800-2000 sccm, the mass flow rate of ammonia is 6000-15000 sccm, the deposition pressure is 1300-2500 mtorr, and the power is 5 kW-20 kW; when the carbon-doped silicon nitride layer 52 is deposited, the mass flow rate of silane is 800-2000 sccm, the mass flow rate of ammonia is 6000-15000 sccm, the mass flow rate of methane is 500-2000 sccm, the deposition pressure is 1300-2500 mtorr, and the power is 5 kW-20 kW. That is, carbon doping of the silicon nitride film layer is achieved by adding methane, thereby forming the carbon-doped silicon nitride layer 52.

[0044] Optionally, the refractive index N of the silicon nitride layer 51 and the carbon-doped silicon nitride layer 52 in the stacked anti-reflection layer 5 has a certain positive correlation with the etching rate C1 (Å / S) thereof in HF, specifically: The etching rate relationship between the refractive index of the silicon nitride layer 51 and the carbon-doped silicon nitride layer 52 in 5% HF is: N = 1.91 + 0.0319*C1 + 1.461*(C1~0.79125) 2 + 5.427*(C1~0.791) 3 .

[0045] By adjusting the relationship between the refractive index and the corrosion rate, it is beneficial to control a certain HF cleaning time in the subsequent solution cleaning, thereby improving the cleaning effect of the second semiconductor layer while maintaining a good anti-reflection effect on the front side.

[0046] S6, removing the back side coating and cleaning the second semiconductor opening area.

[0047] The method for removing the back side coating and cleaning the second semiconductor opening area adopts HF acid solution, in which the mass percentage of HF acid in the HF acid solution is 1%-10%, the mass percentage of deionized water is 90%-99%, the processing temperature is 20℃-30℃, and the removal time is 30-500s.

[0048] Optionally, the cleaning time t≤D / (9C2), t is in S, D is the total thickness of the laminated anti-reflection layer 5 in Å, and C2 is the average corrosion rate of the laminated anti-reflection layer 5 in 5% HF acid.

[0049] This embodiment can effectively remove the back-surface coating and maintain the thickness of the front anti-reflection layer by controlling the cleaning time, thereby improving the front anti-reflection effect.

[0050] S7. Forming a second semiconductor layer on the back side of the silicon wafer 1.

[0051] Optionally, the second semiconductor layer is formed by plate CVD, the intrinsic hydrogenated amorphous silicon layer 6 has a thickness of 4-8 nm, the P-type doped amorphous silicon layer or the P-type microcrystalline silicon layer 7 has a thickness of 6-12 nm, and the deposition temperature of the second semiconductor layer is 150-250°C.

[0052] S8, etching an opening on the back side of the silicon wafer 1 for the second time to form a first semiconductor opening region.

[0053] Optionally, the second etching opening is performed by laser, the laser may be ultraviolet or green laser, the pulse width is less than 10ns, and the width of the formed first semiconductor opening region is 200-300um.

[0054] S9, depositing a transparent conductive film layer 8 on the back side of the silicon wafer 1.

[0055] Optionally, a transparent conductive film is deposited on the back of the silicon wafer 1 by physical vapor deposition (PVD) or activated plasma deposition (RPD). The thickness of the transparent conductive film is 40-80 nm. The material of the transparent conductive film can be an indium oxide-based film doped with tin / tungsten / titanium / zinc or an aluminum / boron-doped zinc oxide-based film.

[0056] S10, etching an opening on the back side of the silicon wafer 1 for the third time to form an insulating groove.

[0057] Optionally, an opening is etched on the back of the silicon wafer 1 by mask etching or laser to form an insulating groove W3 between the first semiconductor and the second semiconductor. The width of the insulating groove W3 is 20-100 μm. After etching, the resistance between the first semiconductor and the second semiconductor is greater than 1 KΩ.

[0058] S11 , forming metal electrodes 9 at the first semiconductor opening and the second semiconductor opening on the back side of the silicon wafer 1 , respectively.

[0059] Optionally, a screen printing technique is used to form metal electrodes 9 on the surfaces of the first semiconductor opening region W1 and the second semiconductor opening region W2 on the back side of the silicon wafer 1 .

[0060] In a third aspect, an embodiment of the present invention further provides a battery assembly, comprising: a back-contact solar cell as described in the above embodiment.

[0061] The embodiments of the present invention are described in detail below, which are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0062] Example 1 like Figure 1 As shown, a back contact solar cell comprises: A silicon wafer 1 having a front side and a back side. As a base layer, the silicon wafer 1 is generally polished to improve the bonding strength of subsequent film layers, thereby improving the stability of the film layers. The first semiconductor layer is arranged on the back of the silicon wafer 1. The first semiconductor layer includes a tunneling silicon oxide layer 2 and an N-type doped polysilicon layer 3 formed in sequence on the back of the silicon wafer 1. The first semiconductor layer is separated by a plurality of second semiconductor opening regions W2. The second semiconductor opening regions W2 and the surface of the first semiconductor layer around the second semiconductor opening regions are covered with the second semiconductor layer. A first semiconductor opening region W1 is provided between adjacent second semiconductor opening regions. The first semiconductor opening region W1 separates the second semiconductor layer. The semiconductor film layers of the first semiconductor region and the second semiconductor region eventually form the P region and the N region of the solar cell. A passivation layer 4 and a stacked anti-reflection layer 5, wherein the passivation layer 4 and the stacked anti-reflection layer 5 are sequentially arranged on the front side of the silicon wafer 1; wherein the stacked anti-reflection layer 5 comprises a silicon nitride layer 51 and a carbon-doped silicon nitride layer 52, wherein the silicon nitride layer 51 is closer to the passivation layer 4 than the carbon-doped silicon nitride layer 52; the total thickness of the stacked anti-reflection layer 5 is 110 nm, wherein the thickness of the silicon nitride layer 51 is 80 nm, and the refractive index is 2.1; the thickness of the carbon-doped silicon nitride layer 52 is 30 nm, and the refractive index is 1.8.

[0063] The present invention also provides a method for preparing the above-mentioned back contact solar cell. In the method, when forming the carbon-doped silicon nitride layer 52 of the laminated anti-reflection layer 5 on the front side of the silicon wafer 1, the mass flow rate of silane is 1200 sccm, the mass flow rate of ammonia is 10800 sccm, the mass flow rate of methane is 1200 sccm, the deposition pressure is 1700 mtorr, the power is 12 kW, and the carbon doping concentration is 8.5×10 18 cm -3 .

[0064] Example 2 Referring to the back contact solar cell of Example 1, the difference is that the total thickness of the stacked anti-reflection layer 5 is 80 nm, and the thickness of the silicon nitride layer 51 is 50 nm.

[0065] Example 3 Referring to the back contact solar cell of Example 1, the difference is that the thickness of the silicon nitride layer 51 is 60 nm, and the thickness of the carbon-doped silicon nitride layer 52 is 50 nm.

[0066] Example 4 Refer to the back contact solar cell of Example 1, except that the refractive index of the silicon nitride layer 51 is 1.95.

[0067] Example 5 Refer to the back contact solar cell of Example 1, except that the refractive index of the carbon-doped silicon nitride is 1.9.

[0068] Example 6 Referring to the back contact solar cell of Example 1, the difference is that the carbon content in the carbon-doped silicon nitride layer 52 is 1.2×10 18 cm -3 .

[0069] Example 7 Referring to the back contact solar cell of Example 1, the difference is that when the carbon nitride silicon layer 52 is doped, the deposition pressure is 1400 mtorr and the power is 9.5 kW.

[0070] Example 8 Referring to the back contact solar cell of Example 1, the difference is that when the carbon nitride silicon layer 52 is doped, the deposition pressure is 1800 mtorr and the power is 16.5 kW.

[0071] Comparative Example 1 Referring to the back contact solar cell of Example 1, the difference is that no carbon-doped silicon nitride layer 52 is provided, that is, the entire layer is silicon nitride layer 51 .

[0072] Comparative Example 2 Referring to the back contact solar cell of Example 1, the difference is that the anti-reflection layer only has a carbon-doped silicon nitride layer 52, the thickness of the carbon-doped silicon nitride layer 52 is 110 nm, and the refractive index is 1.8.

[0073] Comparative Example 3 Referring to the back-contact solar cell of Example 1, the difference is that the total thickness of the stacked anti-reflection layer 5 is 150 nm, and the thickness of the silicon nitride is 140 nm.

[0074] Comparative Example 4 Referring to the back-contact solar cell of Example 1, the difference is that the total thickness of the stacked anti-reflection layer 5 is 70 nm, and the thickness of the silicon nitride is 20 nm.

[0075] Comparative Example 5 Referring to the back contact solar cell of Example 1, the difference is that the carbon content in the carbon-doped silicon nitride layer 52 is 1.9×10 20 cm -3 .

[0076] Test Case The performance of the back contact solar cells obtained in the above examples and comparative examples (including: thickness uniformity of the anti-reflection layer after passing through the solution, current density, open circuit voltage and conversion efficiency) was tested, and the specific test results are shown in Table 1. Among them, the thickness uniformity of the anti-reflection layer after passing through the solution = (maximum value - minimum value) / (maximum value + minimum value) of the film thickness.

[0077] Table 1 Comparison of battery performance of different embodiments and comparative examples

[0078] It can be seen from the above results that, compared with the comparative example, the embodiment scheme of the present invention can take into account both the uniformity of the film thickness and the electrical performance of the battery, which is beneficial to the stability of the efficiency. Furthermore, according to Examples 1 and 2 to 8, it can be seen that the preferred laminated anti-reflection layer scheme of the present invention can ensure the uniformity of the film thickness, which is more conducive to improving the conversion efficiency of the battery.

[0079] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A back contact solar cell, characterized in that: include: A silicon wafer having a front side and a back side; A first semiconductor layer is arranged on the back side of the silicon wafer, the first semiconductor layer comprises a tunneling silicon oxide layer and an N-type doped polysilicon layer sequentially formed on the back side of the silicon wafer; the first semiconductor layer is separated by a plurality of second semiconductor opening regions, the second semiconductor opening regions and the surface of the first semiconductor layer around the second semiconductor opening regions are covered with the second semiconductor layer; a first semiconductor opening region is provided between adjacent second semiconductor opening regions, the first semiconductor opening region separates the second semiconductor layer; A passivation layer and a stacked anti-reflection layer, wherein the passivation layer and the stacked anti-reflection layer are sequentially arranged on the front side of the silicon wafer; wherein the stacked anti-reflection layer comprises a silicon nitride layer and a carbon-doped silicon nitride layer, and the silicon nitride layer is closer to the passivation layer than the carbon-doped silicon nitride layer; the total thickness of the stacked anti-reflection layer is 80-130 nm, wherein the thickness of the silicon nitride layer is 50-120 nm, and the refractive index is 1.9-2.2; the thickness of the carbon-doped silicon nitride layer is 1-50 nm, and the refractive index is 1.7-1.

9.

2. The back contact solar cell according to claim 1, characterized in that: The carbon-doped silicon nitride layer is a carbon-doped silicon nitride film layer with the same concentration throughout the layer, and the carbon doping concentration is 1×10 18 ~9×10 19 cm -3 .

3. The back contact solar cell according to claim 1, characterized in that: The carbon doping concentration of the carbon-doped silicon nitride layer gradually increases from the side close to the silicon wafer to the side away from the silicon wafer, and the carbon doping concentration ranges from low to high, and is 1×10 18 ~9×10 19 cm -3 .

4. The back contact solar cell according to claim 1, characterized in that: The first semiconductor layer includes a tunneling silicon oxide layer and an N-type doped polysilicon layer. The thickness of the tunneling silicon oxide layer is 1-2 nm, and the thickness of the N-type doped polysilicon layer is 80-140 nm.

5. The back contact solar cell according to claim 1, characterized in that: The width of the first semiconductor opening region is 400 μm to 600 μm, and the width of the second semiconductor opening region is 200 μm to 300 μm.

6. The back contact solar cell according to claim 1, characterized in that: Also includes: Insulation slot; The insulating groove is located between the adjacent first semiconductor opening region and the second semiconductor opening region; The first semiconductor opening region and the second semiconductor layer are both covered with a transparent conductive film layer, and the insulating groove separates the transparent conductive film layer located in the first semiconductor opening region from the transparent conductive film layer located on the second semiconductor layer.

7. A method for preparing a back-contact solar cell, for preparing the back-contact solar cell according to any one of claims 1 to 6, characterized in that: include: S1. Provide a double-sided polished silicon wafer; S2, forming a first semiconductor layer and a mask layer on the back side of the silicon wafer; S3, etching an opening on the back side of the silicon wafer for the first time to form a second semiconductor opening region; S4, texturing and cleaning the front and back opening areas of the silicon wafer; S5, forming a passivation layer and a laminated anti-reflection layer on the front side of the silicon wafer; the laminated anti-reflection layer comprises a silicon nitride layer and a carbon-doped silicon nitride layer sequentially formed on the passivation layer; The deposition temperature of the stacked anti-reflection layer is 350-600° C., wherein when depositing the silicon nitride layer, the mass flow rate of silane is 800-2000 sccm, the mass flow rate of ammonia is 6000-15000 sccm, the deposition pressure is 1300-2500 mtorr, and the power is 5 kW-20 kW; when depositing the carbon-doped silicon nitride layer, the mass flow rate of silane is 800-2000 sccm, the mass flow rate of ammonia is 6000-15000 sccm, the mass flow rate of methane is 500-2000 sccm, the deposition pressure is 1300-2500 mtorr, and the power is 5 kW-20 kW; S6, removing the back side coating and cleaning the second semiconductor opening area; The method of removing the back side coating and cleaning the second semiconductor opening area adopts HF acid solution, wherein the mass percentage of HF acid in the HF acid solution is 1% to 10%, the mass percentage of deionized water is 90% to 99%, the processing temperature is 20° C. to 30° C., and the removal time is 30 to 500 seconds; S7, forming a second semiconductor layer on the back side of the silicon wafer; S8, etching an opening on the back side of the silicon wafer for the second time to form a first semiconductor opening region; S9, depositing a transparent conductive film layer on the back side of the silicon wafer; S10, etching an opening on the back side of the silicon wafer for the third time to form an insulating groove; S11, forming metal electrodes at the first semiconductor opening and the second semiconductor opening on the back side of the silicon wafer respectively.

8. The method for preparing a back-contact solar cell according to claim 7, characterized in that: The refractive index N of the silicon nitride layer and the carbon-doped silicon nitride layer in the stacked anti-reflection layer has a certain positive correlation with the corrosion rate C1 (Å / S) thereof in HF, specifically: The etching rate relationship between the refractive index of the silicon nitride layer and the carbon-doped silicon nitride layer in 5% HF is: N = 1.91 + 0.0319*C1 + 1.461*(C1~0.79125) 2 + 5.427*(C1~0.791) 3 。 9. The method for preparing a back-contact solar cell according to claim 7, characterized in that: The cleaning time t≤D / (9C2), t is in S, D is the total thickness of the laminated anti-reflection layer in Å, and C2 is the average corrosion rate of the laminated anti-reflection layer in 5% HF acid.

10. The method for preparing a back contact solar cell according to claim 8, characterized in that: In step S4, it includes: The texturing liquid for texturing cleaning is a mixture of potassium hydroxide or sodium hydroxide, texturing additives and water, wherein the mass percentage of potassium hydroxide or sodium hydroxide is 1%~5%, the mass percentage of texturing additives is 0.5%~1%, the texturing time is 10~60 minutes, and the texturing temperature is 70℃~85℃.

11. The method for preparing a back-contact solar cell according to claim 8, characterized in that: In step S4, it also includes: During the texturing and cleaning process, the first mask layer on the back of the silicon wafer is also removed through the final cleaning solution. The solution used to remove the first mask layer is HF acid solution. The mass percentage of HF acid in the HF acid solution is 0.5%~5%, the mass percentage of hydrogen peroxide is 3%~10%, and the mass percentage of deionized water is 95%~99.5%. The processing temperature is 20℃~30℃, and the removal time is 60s~500s.

12. A battery assembly, characterized in that: include: A back-contact solar cell as claimed in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Shallow groove isolating structure manufacturing method

    CN103295950A

  • Method for forming lamination structure and method for forming interconnection structure

    CN104979268A

  • Back contact battery with specific front passivation structure and preparation method and application thereof

    CN117577697A

  • Selective etching solution of carbon-doped silicon nitride / silicon oxide

    CN119120026A

  • Back contact solar cell, preparation method thereof and cell module

    CN119317234A

Cited By

  • Anti-ultraviolet-attenuation front-side composite passivation anti-reflection film layer and preparation method and application thereof

    CN121398262A